Soil micromorphology of archaeological deposits: with particular reference to floor surfaces on settlement sites in the Western Isles, Scotland - Tams, Adrian Ronald (The University of Edinburgh, 2003)
The research is concerned with the analysis of four field identified floors from three multi-period archaeological sites (Bostadh Beach, Isle of Lewis, Cladh Hallan and Bornais, South Uist) in the Western Isles, Scotland.

The method employed in the analysis of these four floors is soil micromorphology, a technique that is now established in archaeological analysis, but one that has been seldom applied to deposits in the Western Isles. In particular, the application of the technique to floor sequences in the Western Isles is unique, given that floors have rarely been analysed or even substantially documented in archaeological excavations of structures in the islands.

There are three main aims in the analysis of these floors: 1) to highlight the significance and importance of microscale analysis of floors, 2) to determine their composition, formation and possible use, 3) to establish microstructural criteria and characterisation of different materials used for floors.

The analysis has revealed that the floors between the three different sites are extremely different. At Bostadh, the floors are dominated by highly organic materials, whilst Cladh Hallan and Bornais floors are sand dominated with fine organic matter. The most interesting feature of the analysis is that a floor which has been described as a singular deposit in the field, can be composed of upto 21 individual floor layers. This has implications for the information that a potential floor deposit can yield, particularly with regard to the function and use of space within a structure over a depositional sequence.

Micromorphological descriptions followed the international terminology of Bullock et al (1985) and Fitzpatrick (1984), with some adaptations. Organic description has detailed that different types of peat were used at Bostadh, whilst mineralogical analysis has indicated the possibility of cleaning or abandonment episodes. Analysis at Cladh Hallan has aided in the interpretation of the use of space within the structure, although these results only form part of on-going research elsewhere.

The research has successfully described micromorphological characteristics of floors developed from two different materials, and has highlighted the implications and importance for the archaeological record of a settlement, through the analysis of floors. Recommendations concerning the collection and sampling for future floors have also been made.